2005
DOI: 10.1074/jbc.m502810200
|View full text |Cite
|
Sign up to set email alerts
|

Self-association of Transmembrane α-Helices in Model Membranes

Abstract: Interactions between transmembrane helices play a key role in almost all cellular processes involving membrane proteins. We have investigated helix-helix interactions in lipid bilayers with synthetic tryptophan-flanked peptides that mimic the membrane spanning parts of membrane proteins. The peptides were functionalized with pyrene to allow the self-association of the helices to be monitored by pyrene fluorescence and Trp-pyrene fluorescence resonance energy transfer (FRET). Specific labeling of peptides at ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 44 publications
2
65
0
1
Order By: Relevance
“…4 Using a Trp-flanked poly-(Leu-Ala) stretch of variable length (WALP), Killian and co-workers showed that dimerization was almost exclusively antiparallel, not parallel. 18,20 Dimerization of helical peptides with a sequence of (AALALAA) 3 also exhibits dependency on the lipid tail length, 5 allowing for analysis of the contribution of enthalpy and entropy. In computational chemistry, many studies have analyzed TM helix dimerization of glycophorin A (GpA), 10,13,[21][22][23][24][25] whereas relatively few studies have analyzed peptides with simple sequences, except WALP and Lys-flanked poly-(Leu-Ala) (KALP) peptides.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…4 Using a Trp-flanked poly-(Leu-Ala) stretch of variable length (WALP), Killian and co-workers showed that dimerization was almost exclusively antiparallel, not parallel. 18,20 Dimerization of helical peptides with a sequence of (AALALAA) 3 also exhibits dependency on the lipid tail length, 5 allowing for analysis of the contribution of enthalpy and entropy. In computational chemistry, many studies have analyzed TM helix dimerization of glycophorin A (GpA), 10,13,[21][22][23][24][25] whereas relatively few studies have analyzed peptides with simple sequences, except WALP and Lys-flanked poly-(Leu-Ala) (KALP) peptides.…”
Section: Introductionmentioning
confidence: 98%
“…16 On the other hand, analyses using TM peptides with simple sequences showed robust association of helices, even without specific recognition motifs. 17,18 Although many studies cannot be listed here, studies using electron spin resonance have reported that Leu-rich peptides are a) Author to whom correspondence should be addressed. Electronic mail:…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, well-known that the membrane plays an important role in determining the tilt of TM helices [13][14][15][16][17][18][19] and also in mediating the interactions between TM helices. 15,[20][21][22][23][24][25] These phenomena are driven by the hydrophobic mismatch, which is dened as the difference between the hydrophobic length of a helix and the hydrophobic thickness of the membrane it is embedded in. It is reasonable to expect that the membrane, and hence the hydrophobic mismatch, also plays a role in the helix-helix packing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, helix-helix association was also found to depend on the lipid environments in a modelmembrane system, e.g. the bilayer thickness and peptide/ lipid ratios [26]. Our present study indicated that even incorporation sequences of loops would affect aggregation states of transmembrane domains in micelles.…”
Section: Discussionmentioning
confidence: 79%
“…Interactions between transmembrane helices play a key role in almost all cellular processes involving membrane proteins. Previous studies demonstrated that the association between transmembrane helices to form oligomers was promoted by unfavorable protein-lipid interactions [26]. Such association would lead to polar or charged residues in the membrane apolar core to be stabilized by ionic force, hydrogen bonds and the interstitial water molecules between polar residues in the interior of the membrane helix bundle [27].…”
Section: Discussionmentioning
confidence: 99%